2019
DOI: 10.3389/fphys.2019.01499
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a Low-Carbohydrate High-Fat Diet and a Single Bout of Exercise on Glucose Tolerance, Lipid Profile and Endothelial Function in Normal Weight Young Healthy Females

Abstract: Low-carbohydrate-high-fat (LCHF) diets are efficient for weight loss, and are also used by healthy people to maintain bodyweight. The main aim of this study was to investigate the effect of 3-week energy-balanced LCHF-diet, with >75 percentage energy (E%) from fat, on glucose tolerance and lipid profile in normal weight, young, healthy women. The second aim of the study was to investigate if a bout of exercise would prevent any negative effect of LCHF-diet on glucose tolerance. Seventeen females participated, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
22
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 111 publications
2
22
0
1
Order By: Relevance
“…Notably, ketogenic LCHF diet interventions in healthy, normal-weight humans that measured serum biomarkers for CVD are dominated by men. There is a single study with only women [ 22 ] and, although some of the other studies [ 23 , 24 , 25 ] include both healthy women and men, data are disaggregated by sex in only one intervention [ 23 ]. There are well-known sex-specific differences in metabolic physiological systems, caused by the inherently different biology of the two sexes.…”
Section: Introductionmentioning
confidence: 99%
“…Notably, ketogenic LCHF diet interventions in healthy, normal-weight humans that measured serum biomarkers for CVD are dominated by men. There is a single study with only women [ 22 ] and, although some of the other studies [ 23 , 24 , 25 ] include both healthy women and men, data are disaggregated by sex in only one intervention [ 23 ]. There are well-known sex-specific differences in metabolic physiological systems, caused by the inherently different biology of the two sexes.…”
Section: Introductionmentioning
confidence: 99%
“…Previous LCHF studies with weight loss have resulted in increased LDL at six weeks [ 63 ] and three months [ 16 ]. Our recent study on normal-weight young women has shown that an LCHF diet high in saturated fat increased LDL levels in this group to levels above the target for primary prevention in only three weeks [ 17 ]. These results are supported by meta-analyses that concluded that LCHF diets, even with a pronounced weight-loss, resulted in an increase in LDL [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…The between-group comparison showed a significant improvement in LDL in the NORM-EX group compared to the LCHF-EX group after the intervention. This result was not expected as the combination of weight-loss and exercise was expected to counteract the effect of higher intake of fats, including saturated fats, in the LCHF groups ( Table 4 ) [ 17 , 63 ]. It has to be taken into consideration that there is an ongoing debate as to whether the size of the LDL particles is of importance in regard to CVD risk and it has been proposed that risk prediction may be improved by using information on LDL particle number and size [ 66 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A case-control study shows that ketogenic diet can promote arterial stiffening and endothelial damage in children and young adults with epilepsy [ 105 ]. In addition, LCHFD shows no improvement of endothelial function (flow-mediated dilation) in normal weight, young, healthy women [ 106 ], while LCHFD may lead to a reduction in flow-mediated dilation and predispose the endothelium to hyperglycemia-induced damage in healthy young adults [ 107 ]. Indeed, the detrimental effect of ketogenic diet may be attributed to the formation of advanced glycation end (AGE) products, which promote vascular damages [ 108 ].…”
Section: Diet Effect On Endothelial Function and Oxidative Stressmentioning
confidence: 99%